Implementation of Local Knwoledge “Tri Hita Karana” on Ecotour-ISM Management in Bali - SUryawan Wiranatha, Agung; Gde Raka Dalem, Anak Agung (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 10, No. 1 Februari 2010, 2010)
-